PENGARUH JENIS DAN JUMLAH ADSORBEN SERTA LAMA PERENDAMAN TERHADAP CUKA KAYU UNTUK PENGAWET MAKANAN (The Effect of Type And Amount of Adsorbent and Soaking Time to The Characteristics of Wood Vinegar for Food Preservatives) - Rizka Karima; Fatmi Edwar (Kementerian Perindustrian, 2016)
Wood vinegar contains antibacterial compounds and antioxidants which is important as preservative in the food industry. This research aims to identify the characteristics of wood vinegar after deodorized, because the smell of wood vinegar spoils the odour of foods preserved with wood vinegar. The deodorizing used three types of adsorbent such as bentonite, active sand and zeolite. It was performed with three variations of weight: 10, 25, and 50 grams, and three variations of the soaking time: 2, 4, and 6 hours. The deodorised wood vinegar was organoleptically tested by 20 panelists to smell the deodorised wood vinegar. The five smallest samples were tested from the total 27 samples. However, the fifth and sixth were the same so the total sample tested was six samples. The physical and chemical testing results stated that the treated wood vinegar odor reduction has changed the chemical content, decreased the levels of total acids about 69,35 %, and decreased the phenol content about 51,51 %. It resulted in the obtained values did not meet the standard quality of wood vinegar. From the results of GC-MS spectra, there are entrained Silica that dissolved in the wood vinegar after deodorizing. In conclusion, the adsorbent able to eliminate the odor but degrade the quality of wood vinegar.Keywords: food preservative, wood vinegar, adsorbent